Production of a polyclonal antibody against acrylamide for immunochromatographic detection of acrylamide using strip tests (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: To produce, purify, and characterize a polyclonal antibody against acrylamide (anti-AA) for an application to immunochromatographic strip tests for AA.Material and Methods: Polyclonal anti-AA was prepared by injecting N-acryloxysuccinimide-conjugated bovine serum albumin hapten-antigen into New Zealand white rabbits. The antibody was purified using protein A, characterized using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and conjugated with gold nanoparticles (AuNP). The conjugated antibody was then characterized using UV–Vis and FTIR spectroscopy and transmission electron microscopy (TEM). Immunochromatographic strip tests were performed using sample pads, conjugated pads, test zones, control zones, and absorbent pads. Strip tests were finally validated using standard AA solutions followed by the application of various concentrations of coffee samples.Results: Using SDS-PAGE, the purified anti-AA antibody was resolved at 50 and 25 kDa, indicating the presence of heavy and light chains, respectively. The conjugation of anti-AA with AuNP was confirmed using wavelength shifts in UV–Vis and FTIR spectra, and TEM analyses revealed increased diameters of AuNPs after conjugation. The immunochromatographic strip test was sensitive to 1 mgml−1 standard AA. Various concentrations of coffee samples resulted in red color differences in the test zone. High and low coffee concentrations produced thick and thin red lines, respectively.Conclusion: Purified anti-AA can be conjugated with AuNP to produce strip tests for detecting AA in coffee samples. The present immunochromatographic strip tests quantitatively showed increasing intensities of red lines with increasing AA concentrations.J. Adv. Vet. Anim. Res., 6(3): 366-375, September 2019